Seed dormancy of Ochradenus baccatus (Resedaceae), a shrubby species from Arabian desert regions - Bhatt, Arvind; Pérez-García, Félix (Revista de Biología Tropical, 2016)
Ochradenus baccatus is a perennial glycophyte growing in Middle East and it is one of the most important food sources for many animal species in desert regions. The aim of our study was to investigate the effects of seed storage, light, temperature and gibberellic acid (GA3) on germination of O. baccatus seeds. We also investigated the germination characteristics of O. baccatus seeds under different saline concentration and their capability to recover germination once they were transferred to distilled water. Seeds were stored at room temperature (20 ± 2 ºC) and at -18 ºC. Germination tests were conducted at alternating temperatures of 15/25, 20/30 and 25/35 ºC in either continuous darkness or photoperiod of 12-h dark/12-h light. To study the effect of GA3 on germination of O. baccatus seeds, freshly-collected seeds and stored seeds were soaked for 24 h in a GA3 water solution (1 g/L) before sowing. To assess the salinity tolerance during germination, seeds were germinated under different salinity levels (100, 200 and 400 mM NaCl). Stored seeds at room temperature and -18 ºC germinate equally well at different temperature regimes and light conditions. However, freshly matured seeds were not able to germinate even when they were treated with GA3. On the contrary, stored seeds at room temperature and -18 ºC treated with GA3 increase the final germination percentages. These results indicated that O. baccatus seeds have physiological dormancy and they need to be stored in order to break their dormancy. In the present study, one year of storage did not show a significant variation in germination between the two storage conditions assayed. Therefore, further research is needed to know about the maximum storage period for O. baccatus seeds under different storage conditions. Very few O. baccatus seeds (less than 5 %) germinated at the tested lowest concentration of NaCl. However, ungerminated seeds were able to germinate when salinity stress was alleviated. In conclusion, O. baccatus seeds have physiological dormancy, and seed storage (at room temperature and at -18 ºC) for one year is effective for breaking this dormancy. In addition, O. baccatus seeds present ability to remain viable in saline conditions and they will be able to germinate once the salinity level decrease.